(untitled) (Bombay Hospital Journal, 2024)
Cerebral fat embolism syndrome is a known complication following polytrauma especially fracture of long bones, but cardiac arrest is rare presentation following cerebral fat embolization. Our patient met with Road Traffic Accident (RTA), sustaining multiple long bones injury with hypovolemic shock. After 10 hours of admission and achieving hemodynamic stability, patient developed cerebral fat embolization. He developed sudden cardiac arrest and he was resuscitated. Instituted ventilator support, inotropic infusion, antibiotics and IV fluids. Our patient regained consciousness without neurological deficit over a period of 10 days and underwent surgery for all three major fractures with due precautions. Patient was discharged after 3 weeks of treatment from the hospital.